Graphene nanocoating provides superb long-lasting corrosion protection to titanium alloy. Issue 10 (October 2021) - Malhotra, Ritika; Han, Yingmei; Nijhuis, Christian A.; Silikas, Nikolaos; Castro Neto, A.H.; Rosa, Vinicius
Graphical abstract: Abstract: Objective: The presence of metallic species around failed implants raises concerns about the stability of titanium alloy (Ti-6Al-4V). Graphene nanocoating on titanium alloy (GN) has promising anti-corrosion properties, but its long-term protective potential and structural stability remains unknown. The objective was to determine GN's anti-corrosion potential and stability over time. Methods: GN and uncoated titanium alloy (Control) were challenged with a highly acidic fluorinated corrosive medium (pH 2.0) for up to 240 days. The samples were periodically tested using potentiodynamic polarization curves, electrochemical impedance spectroscopy and inductively coupled plasma-atomic emission spectroscopy (elemental release). The integrity of samples was determined using Raman spectroscopy, X-ray photoelectron spectroscopy, atomic force microscopy and scanning electron microscopy. Statistical analyses were performed with one-sample t-test, paired t-test and one-way ANOVA with Tukey post-hoc test with a pre-set significance level of 5%. Results: There was negligible corrosion and elemental loss on GN. After 240 days of corrosion challenge, the corrosion rate and roughness increased by two and twelve times for the Control whereas remained unchanged for GN. The nanocoating presented remarkably high structural integrity and coverage area (>98%) at all time points tested. Significance: Graphene nanocoating protects titanium alloy from corrosion and dissolution over a long period while maintaining high structural integrity. This coating has promising potential for persistent protection of titanium and potentially other metallic alloys against corrosion.